PENGARUH WORK-FAMILY CONFLICT TERHADAP WORK ENGAGEMENT YANG DIMEDIASI OLEH EMPLOYEE RESILIENCE - Yuni Wulandari; Praptini Yulianti (Value : Jurnal Manajemen dan Akuntansi, 2023)
Work Engagement is currently needed by organizations in dealing with all the changes that are so fast. The increase in the number of female workers, especially those with mother status, is also an organizational challenge in managing the WFC that occurs. Organizations must support the creation of employee resilience which is expected to be able to maintain the Work Engagement of employees who experience WFC. This research was conducted to find out how the influence of Work-family conflict on Work Engagement is mediated by Employee Resilience. The research respondents were 491 BPS female employees in East Java. This study used a purposive sampling method, with a representative sample of 194 employees. In this research, collecting data used a Google Form questionnaire which was distributed via e-mail and private networks. Data processing using SEM-PLS with Smart PLS 3.2.9. Based on the results of the analysis and discussion, it is known that Employee Resilience mediates the relationship between Work-Family conflict and Work Engagement. A working mother who has self-toughness will be able to suppress the WFC that occurs to stay engaged at work. Keywords: WFC, Work Engagement, Employee Resilience